Help! What's eating my flesh? : runaway staph and strep infections! - Tilden, Thomasine E. Lewis, 1958- (New York, NY : Franklin Watts, 2008)
Bacteria are the most common living things on earth and you carry them wherever you go. Most of them couldn't hurt a flea, but if conditions are just right, they can cause big problems!
"True-life cases!"--Cover.
Includes bibliographical and internet references (p. 57-58) and index.
G4
Keywords: Staphylococcal infections -- Juvenile literature; Necrotizing fasciitis -- Juvenile literature; Streptococcal infections -- Juvenile literature; Staphylococcal infections; Necrotizing fasciitis; Streptococcal infections